Croatian-Hungarian trans-border relationships from state socialism until today, with special attention to the euroregions - Bali, Lóránt (Jelenkori Társadalmi és Gazdasági Folyamatok, 2008)
On the whole we can claim that in the last almost sixty years there was a significant change in Croatian-Hungarian trans-border relationships. State-governed cooperation was replaced by project-controlled co-operations under the guidance of local-governments and the civil sphere. Unfortunately, stock and human workforce deficit very often obstructs success. Besides it is a permanent problem in our country that state politics has a great influence on local-government politics. So in a certain euroregion the success of operation highly depends on where the local-governments and civil organization belong to politically and on the leaders' ability to validate their interests. As a result of stock deficit mentioned previously project-based co-operations occurred.1 But these ad hoc project associations are not able and won't even be able to use union sources efficiently and generate any kind of long-term regional development.